2016
DOI: 10.5530/pj.2016.6.2
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of n-hexane Extract of Stem Bark of Symplocos crataegoides Buch.-Ham. ex D. Don

Abstract: The stem bark of the plant Symplocos crataegoides Buch.-Ham. ex D. Don, Fam. Symplocaceae is extensively used in Indian medicine under the names of Lodhra/Patikalodhra. S. crataegoides is a deciduous shrub or a tree, distributed in the Himalayas from Punjab to Assam, Khasi hills and Burma. 1,2 As per Ayurvedic references the term Lodhra denotes the stem bark of Symplocos racemosa/Symplocos crataegoides and considered as most useful remedy for uterine complaints, vaginal and menstrual disorders. In Sanskrit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Germacrene D-4-ol (Gillij et al, 2008), hexadecanoic acid (Pino et al, 2003), and octadecanoic acid (Shah & Khan, 2017) without their esters were identified in essential and the methanol (ethyl acetate) extract. In the line of our results, tetradecane, caryophyllene oxide, hexadecanoic acid, caryophyllene, germacrene D, 9, 12-octadecadienoic acid, methyl ester, oleic acid, phytol, tetradecane, squalene, heneicosane, and methyl derivatives have been identified by GC-MS analysis in the n-hexane fraction/extract of different plant species (Godwin et al, 2015;Govindarajan et al, 2016;Ivanov et al, 2018;Nadaf et al, 2012). It has been observed that in the n-hexane fraction or extract of different plants, there is a remarkable variability of compounds, particularly the methyl esters.…”
Section: Phytochemical Iden Fica Onsupporting
confidence: 82%
“…Germacrene D-4-ol (Gillij et al, 2008), hexadecanoic acid (Pino et al, 2003), and octadecanoic acid (Shah & Khan, 2017) without their esters were identified in essential and the methanol (ethyl acetate) extract. In the line of our results, tetradecane, caryophyllene oxide, hexadecanoic acid, caryophyllene, germacrene D, 9, 12-octadecadienoic acid, methyl ester, oleic acid, phytol, tetradecane, squalene, heneicosane, and methyl derivatives have been identified by GC-MS analysis in the n-hexane fraction/extract of different plant species (Godwin et al, 2015;Govindarajan et al, 2016;Ivanov et al, 2018;Nadaf et al, 2012). It has been observed that in the n-hexane fraction or extract of different plants, there is a remarkable variability of compounds, particularly the methyl esters.…”
Section: Phytochemical Iden Fica Onsupporting
confidence: 82%
“…Undecane was previously identified as a major constituent of the extract of the stem bark of Symplocos crataegoides Buch.-Ham. ex D. Don (7.5%) [ 37 ], Opuntia ficus indica (L.) Mill (20%) [ 38 ], Seseli pallasii Besser (13.3%), T. baccata (12.2%) [ 29 ], and in smaller percentages in the essential oils of Hypericum hirsutum L. [ 39 ] and Lantana camara L. [ 40 ]. There is no clear information available on the mechanism of action of undecane as an antimicrobial agent.…”
Section: Discussionmentioning
confidence: 99%
“…brunneum (Pereira et al, 2019). Dodecano presente apenas em P. clavata é relatado pela primeira vez em formigas, sendo encontrado em extratos da casca de planta medicinal nativa da Ásia Symplocos crataegoides (Govindarajan et al 2016). Dodecano, n-Heptadecano, n-Nonadecano e n-Pentacosano foram identificados no extrato de três espécies de Hypericum, uma planta medicinal, com atividade antidepressiva, antinociceptiva e antimicrobiana (Zorzetto et al, 2015).…”
Section: Volatilômicaunclassified